Does the transcultural problem really matter? An integrated approach to analyze barriers to eHealth SMEs’ development - Guoqing Zhao (International Journal of Entrepreneurial Behavior & Research, 2023)
Purpose: In a competitive environment, eHealth SMEs’ barriers to survival differ from those of large enterprises. Empirical research on barriers to eHealth SME’s in less prosperous areas has been largely neglected. This study fills this gap by employing an integrated approach to analyze barriers to the development of eHealth SMEs. Design/methodology/approach: We collected data through semi-structured interviews, and conducted thematic analysis to identify 16 barriers, which were used as inputs into total interpretive structural modeling (TISM) to build interrelationships among them and identify key barriers. Cross-impact matrix multiplication applied to classification (MICMAC) was then applied validate the TISM model and classify the 16 barriers into four categories. Findings: This study makes significant contributions to theory by identifying new barriers and their interrelationships, distinguishing key barriers, and classifying the barriers into four categories. We identify that transcultural problems are the key barrier and deserve particular attention. eHealth SMEs originating from regions with cultural value orientations, such as hierarchy and embeddedness, that differ from the UK’s affective autonomy orientation should strengthen their transcultural awareness when seeking to expand into UK markets. Originality/value: By employing an integrated approach to analyze barriers that impede the development of eHealth SMEs in a less prosperous area of the UK, this study raises entrepreneurs’ awareness of running businesses in places with different cultural value orientations.